A CFD analysis of the aerodynamics of a high-speed train passing through a windbreak transition under crosswind. Issue 1 (1st January 2018) - Liu, Tanghong; Chen, Zhengwei; Zhou, Xisai; Zhang, Jie
ABSTRACT: In areas with strong wind, windbreaks are built along railways to reduce the impact of wind on trains. However, because of the restrictions imposed by actual terrain, windbreak structures are often not uniform, such as from a cutting to an embankment, resulting in a discontinuous transition region. When a train runs through this region, a distinct yawing phenomenon occurs. This study numerically explored the aerodynamic features of a train running through a rectangular windbreak transition region. The variations in the pressure, side force, and moment of a train were analyzed, and the flow field features were clarified. Furthermore, the yawing motion of the car body with time was described. Finally, based on EN14067-6, the critical wind speed was obtained using the safety assessment of a train running through a windbreak transition region.